Study on the role and pharmacology of cuproptosis in gastric cancer - Jiang, Lin; Liao, Junzuo; Han, Yunwei (Frontiers in Oncology, 2023)
Objective: The prognosis of gastric cancer is poor and the mortality is high. Cuproptosis as a novel programmed cell death is rarely studied in gastric cancer. Methods: TCGA database is used to obtain transcriptome data of gastric cancer tissues and adjacent tissues. GSE66229 is used for external verification. Overlapping genes were obtained by crossing the genes obtained by differential analysis with those related to copper death. Eight characteristic genes were obtained by three dimensionality reduction methods: lasso, SVM and random forest. ROC and nomogram were used to estimate the diagnostic efficacy of characteristic genes. CIBERSORT method was used to evaluate immune infiltration. ConsensusClusterPlus is used for subtype classification. Discovery Studio software conducts molecular docking between drugs and target proteins. Results: We established the early diagnosis model of eight characteristic genes (ENTPD3, PDZD4, CNN1, GTPBP4, FPGS, UTP25, CENPW, and FAM111A) for gastric cancer. The results are verified by internal and external data, and the prediction effect is good. The subtype classification and immune type analysis of gastric cancer samples were carried out based on the consensus clustering method. We identified C2 as an immune subtype and C1 as a non-immune subtype. Small molecule drug targeting based on genes associated with cuproptosis predicts potential therapeutic agents for gastric cancer. Molecular docking showed that there were multiple forces between Dasatinib and CNN1. Conclusion: The candidate drug Dasatinib may be effective in treating gastric cancer by affecting the expression of the cuproptosis signature gene.